2013
DOI: 10.1590/s1517-83822013005000060
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of the ethanolic extracts of Punica granatum L. and evaluation of the morphological and structural modifications of its compounds upon the cells of Candida spp.

Abstract: Ethanolic crude extracts prepared from the arils and seeds, pericarp, peels and from the whole fruit of Punica granatum, known as pomegranate, had their antifungal activity tested against Candida spp. The ethanolic crude extracts were analyzed by Mass Spectrometry and yielded many compounds such as punicalagin and galladydilacton. The extracts from the pericarp and peel showed activity against Candida spp., with MICs of 125 μg/mL. The effect of pericarp and peel extracts upon the morphological and structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 31 publications
4
46
0
14
Order By: Relevance
“…Several studies have reported the effectiveness of pomegranate extracts against phytopathogenic fungi that cause major economic losses of important crops . Also, some Candida species, which are prevalent and important pathogens detected in hospitalized patients with nosocomial infections, have been treated with ethanolic extracts obtained from arils and seeds, pericarp, and peels, as well as from the whole fruit of pomegranate . Some studies have reported significant inhibitory activity against Candida albicans using pomegranate extracts …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the effectiveness of pomegranate extracts against phytopathogenic fungi that cause major economic losses of important crops . Also, some Candida species, which are prevalent and important pathogens detected in hospitalized patients with nosocomial infections, have been treated with ethanolic extracts obtained from arils and seeds, pericarp, and peels, as well as from the whole fruit of pomegranate . Some studies have reported significant inhibitory activity against Candida albicans using pomegranate extracts …”
Section: Introductionmentioning
confidence: 99%
“…6 -11 Also, some Candida species, which are prevalent and important pathogens detected in hospitalized patients with nosocomial infections, 12 have been treated with ethanolic extracts obtained from arils and seeds, pericarp, and peels, as well as from the whole fruit of pomegranate. 13 Some studies have reported significant inhibitory activity against Candida albicans using pomegranate extracts. 14 -17 Currently, consumers are more concerned about the safety of the synthetic preservatives of food, and research has evaluated alternative natural products against microorganisms that cause food-borne illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…10 Suspensi C. albicans yang setara dengan kekeruhan 0,5 Mc Farland diambil sebanyak 0,1 mL dan ditanam menggunakan cotton bud pada lempeng agar. Sebanyak 5 buah cakram kertas berdiameter 8 mm ditetesi 50 μL fraksi air umbi sarang semut dengan konsentrasi 10.000 μg/mL, 5.000 μg/mL, dan 2.500 μg/mL pada cakram kertas pertama, kedua, dan ketiga, kemudian diteteskan 50 μL nistatin dengan konsentrasi 50 μg/mL ke dalam cakram kertas keempat sebagai kontrol atau pembanding.…”
Section: Metodeunclassified
“…Monitoring the ethanolic extracts from P. granatum by mass spectrometry, Anibal et al (2013) detected various compounds, among them delfinidin 3-O-glucoside, punicacortein A, punicacortein B, pedunculagin, tellimagrandin, glucose, citric acid, caffeic acid, punicic acid (cis-9, trans-11, cis-13 octadecatrienoic acid), ellagic acid, quercetin, delphinidin, gallagyldilacton and punicalagin from pericarp; and punicacortein A, punicacortein B, corilagin, glucose, citric acid, caffeic acid, punicic acid (cis-9, trans-11, cis-13 octadecatrienoic acid), pedunculagin, tellimagrandin and punicalagin from the peels.…”
Section: Medicinal Plants: Punica Granatummentioning
confidence: 99%
“…Anibal (2007) evaluated the activity of the pomegranate through crude extracts dichloromethane and methanolic, against standard strains of C. albicans, C. glabrata, C. krusei, C. parapsilosis, C. tropicalis, C. dubliniensis, C. utilis, C. guilliermondii, C. lusitaniae, and C. rugosa, demonstrating antifungal activity of this plant of interest for alternative therapy against these microorganisms. Anibal et al (2013) showed that ethanolic extracts obtained from pericarp and peel presented potential inhibitory activity, with a minimun inhibitory concentration of 125 µg/ml. These data indicate that the activity of P. granatum probably occurs in the compounds present in the pericarp and peel of this fruit.…”
Section: Resistance To Antifungal Agentsmentioning
confidence: 99%